2022
DOI: 10.1002/pon.5869
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment in cancer patients: Does peer support make a difference? A systematic review

Abstract: Objective Empowerment is critical for cancer patients to make informed choices, to manage medication, and to navigate through the oncological care system. Cancer peer support provides patients with information, emotional relief and may promote empowerment. This paper provides a systematic review of the literature examining the impact of cancer peer support interventions on psychological empowerment. Methods PubMed, Web of Science, CINAHL, Cochrane Library, PsycINFO and PSYNDEX databases were systematically sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 91 publications
2
49
0
Order By: Relevance
“…Patients in our study considered peer support a valuable type of psychosocial support, and previous research has shown it could improve patients’ psychological empowerment (e.g. increased self‐efficacy and positive coping) 49 and enable social reintegration 50 and return to work 51 . Current melanoma SSC does not include psychosocial supportive care and is mainly medically oriented.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in our study considered peer support a valuable type of psychosocial support, and previous research has shown it could improve patients’ psychological empowerment (e.g. increased self‐efficacy and positive coping) 49 and enable social reintegration 50 and return to work 51 . Current melanoma SSC does not include psychosocial supportive care and is mainly medically oriented.…”
Section: Discussionmentioning
confidence: 99%
“…Collaboration with patient organizations may connect different patients experiencing the same issues. Peer support can create connection and empathy that will likely lead to patients feeling better and having better outcomes [38]. It was suggested that cancer patients be provided with a "cancer coach" who would provide them with a road map of their cancer journey and explain the role of different specialists they will encounter, the support they might need, and where and how to get the support needed.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…This is the support of persons who share their experiential knowledge, and/or emotional, social or practical support to others in similar conditions [ 15 ]. Peer support can be provided one-to-one or in a group, it can be professional-led or peer-led, and it can be delivered face-to-face or online [ 16 ]. Online peer support can be asynchronous (such as online discussion boards) or synchronous (through video-conferencing).…”
Section: Introductionmentioning
confidence: 99%
“…Online peer support can be asynchronous (such as online discussion boards) or synchronous (through video-conferencing). For persons with cancer, a recent review indicates that peer-led peer support has positive effects on coping, self-efficacy and cancer-related knowledge, regardless of the mode, duration and format of the intervention [ 16 ]. Most studies in this review were conducted among persons with breast cancer [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation